(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India is an agricultural country. It is also a country with a large amount of natural and human resources. At the same time, it is a country full of geographical diversity. According to the 2011 census, the population of India is 121 crores. This amount is equal to 17 percent of the world’s population. At the same time, the geographical area is 329 D.L. is a hectare. This amount is equal to 2.4 percent of the world. This means that more population is dependent on less land. As a result, increasing population affects the economic development and per capita income of the country. If the per capita income is low, the purchasing power of the people is low. As a result, poverty increases. According to the World Report, 1.3 billion people live in poverty in the world. 36 percent of them live in India.1 According to the Tendulkar Committee report, India had a total poverty rate of 21.9 percent in 2011-12. 25.7 percent of them were in rural areas while 13.7 percent were in urban areas. The same figure was 37.2 percent in India in 2004-05. 41.8 percent of them were in rural areas. While 25.7 percent were in urban areas.2